A comparative study of spinel structured Mn3O4, Co3O4 and Fe3O4 nanoparticles in catalytic oxidation of phenolic contaminants in aqueous solutions - Saputra, E.; Muhammad, S.; Sun, Hongqi; Ang, Ha Ming; Tade, Moses; Wang, Shaobin (Academic Press, 2013)
Spinel structured Mn3O4, Co3O4 and Fe3O4 nanoparticles were prepared, characterized, and tested in degradation of aqueous phenol in the presence of peroxymonosulfate. It was found that Mn3O4 and Co3O4 nanoparticles are highly effective in heterogeneous activation of peroxymonosulfate to produce sulfate radicals for phenol degradation. The activity shows an order of Mn3O4 > Co3O4 > Fe3O4. Mn3O4 could fast and completely remove phenol in about 20 min, at the conditions of 25 ppm phenol, 0.4 g/L catalyst, 2 g/L oxone®, and 25 °C. A pseudo first order model would fit to phenol degradation kinetics and activation energies on Mn3O4 and Co3O4 were obtained as 38.5 and 66.2 kJ/mol, respectively. In addition, Mn3O4 exhibited excellent catalytic stability in several runs, demonstrating that Mn3O4 is a promising catalyst alternative to toxic Co3O4 for water treatment.